Problematika Hukum PayLater dalam Perspektif Fikih Muamalah: Antara Akad Qardh dan Riba - Maximiliania Krismarmitra Brahman; Amelia Nabila Pramesthi; Fadhil Pratama Aryon; Nabila Sanina (Journal of Economic and Business Advancement, 2026)
This study examines the legal problems of PayLater within the framework of Islamic commercial jurisprudence, focusing on the tension between qardh-based structures and the prohibition of riba. Employing a normative-conceptual approach with critical legal analysis, the research evaluates the contractual construction, operational mechanisms, and compliance of PayLater practices with Islamic economic principles. The findings indicate that although PayLater is often presented as a deferred payment system linked to sale transactions, its practical implementation frequently reflects a loan-based structure accompanied by additional charges, thereby falling into the category of riba. From a maqashid al-shariah perspective, such practices pose risks to wealth protection due to the potential accumulation of disproportionate financial burdens. Nevertheless, the study identifies the possibility of reconstructing PayLater into a Sharia-compliant model through appropriate contractual frameworks and transparent profit mechanisms, contributing to the development of ethically aligned financial technology systems.